Comparative assessment of soil bulk density measurements using core metal ring and power probe methods in acidic soils of Colombian pasturelands - Rodriguez, Leonardo; Bastidas, Mike; Da Silva, Mayesse; Arias, Juliana; Martin Lopez, Javier Mauricio; Matiz Rubio, Natalia; Loaiza, Sandra; Idupulapati, Rao; Arango, Jacobo; Costa Junior, Ciniro (Frontiers Media, 2025)
Accurate and cost-effective soil bulk density (BD) measurements are crucial for robust climate mitigation and adaptation strategies by ensuring reliable estimation of key soil properties, such as soil organic carbon (SOC) stocks. This study evaluates the effectiveness of the power probe method compared to the traditional core metal ring method (reference method) for measuring BD in acidic soils (Oxisols and Ultisols) in Colombia. Soil samples were collected from eight locations at soil depths of up to 1 meter, with fine fraction content ranging from 29% to 57% silt and 31% to 41% clay, covering two land uses: natural savanna (n=2) and planted pastures (n=6) (Urochloa humidicola cv. Tully). We found minimal differences between the use of metal ring and probe methods for BD measurements, indicating that both methods generate similar results. Out of 32 observations, only four showed significant differences at specific soil depths with varying silt or clay content. While the probe method showed higher variability, particularly in the 0–10 cm and 50–100 cm layers, which is likely due to soil compaction or stretching, it offers significant advantages in terms of cost reduction and improved work efficiency. While further validation is recommended for use in different soil types and conditions, particularly in clay-rich soils, integrating the use of power probe method in soil assessments can significantly enhance the efficiency of BD measurements. This is particularly relevant to support agricultural and SOC management initiatives while streamlining monitoring efforts for climate finance, where reliable, efficient, and cost-effective soil measurements are crucial.